2000
DOI: 10.1046/j.1432-1327.2000.01589.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of human HtrA2, a novel serine protease involved in the mammalian cellular stress response

Abstract: Human HtrA2 is a novel member of the HtrA serine protease family and shows extensive homology to the Escherichia coli HtrA genes that are essential for bacterial survival at high temperatures. HumHtrA2 is also homologous to human HtrA1, also known as L56/HtrA, which is differentially expressed in human osteoarthritic cartilage and after SV40 transformation of human fibroblasts. HumHtrA2 is upregulated in mammalian cells in response to stress induced by both heat shock and tunicamycin treatment. Biochemical cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
213
2
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 245 publications
(225 citation statements)
references
References 44 publications
(64 reference statements)
8
213
2
2
Order By: Relevance
“…Maintenance of autophagy at a basal level in most cells contributes to the routine turnover of cytoplasmic components, and autophagy is rapidly upregulated when cells need to generate intracellular nutrients and energy. As previously reported, ER stress can activate autophagy 18 and increase Omi expression 4 (confirmed in Supplementary Figure S2a), indicating that endogenous Omi might be involved in regulating constitutive basal autophagy. We therefore examined whether endogenous Omi levels were related to stress-induced autophagy activation.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…Maintenance of autophagy at a basal level in most cells contributes to the routine turnover of cytoplasmic components, and autophagy is rapidly upregulated when cells need to generate intracellular nutrients and energy. As previously reported, ER stress can activate autophagy 18 and increase Omi expression 4 (confirmed in Supplementary Figure S2a), indicating that endogenous Omi might be involved in regulating constitutive basal autophagy. We therefore examined whether endogenous Omi levels were related to stress-induced autophagy activation.…”
Section: Resultssupporting
confidence: 86%
“…Omi is reported to be upregulated by severalfold after heat shock or tunicamycin treatment. 4 In our report, both mRNA and protein levels increased under tunicamycin treatment (Figure 2a; Supplementary Figure S2b). In a mouse model of kidney ischemia/ reperfusion, protease activity of Omi obviously increased.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…The serine protease Omi (also known as high temperature requirement (HtrA2)) was identified first as an interactor of mxi2 or presenilin in human cells (Faccio et al, 2000;Gray et al, 2000) Thereafter, Omi was found to interact with XIAP(X-linked inhibitor of apoptosis). As XIAP was thought to be a direct inhibitor of caspases, the apoptotic function of Omi was extensively investigated.…”
Section: Introductionmentioning
confidence: 99%